Effect of cropping rotation patterns on rice productivity in irrigated rice fields. Issue 1 (April 2021) - Suprihatin, A; Purwanto, B H; Hanudin, E; Nurudin, M
Abstract: Crop rotation has an important role in increasing soil fertility (chemical, physical and biological), production, and sustainable land use. The aim of this study to determine the variables affecting rice productivity in irrigated rice fields in several crop rotation patterns. The fieldwork was taken place in irrigated rice fields, Imogiri District - Bantul, Yogyakarta, Indonesia. The experimental design used in this study was Oversite design, on four irrigated rice fields that applied four different crop rotation patterns: rice-rice-corn (RRM), rice-rice-soybean (RRS), rice-rice-rice ( CCR), and rice-rice-rice grown organically (COR). The rice variety Inpari 23 was grown during wet season (February - May 2018) while during dry season (June – September 2018), the rice variety Mentik Wangi was planted. The data were analyzed by ANOVA at 5% level, and continued with HSD level 5% using SAS 9.1.3. portable, while the correlation analysis used SPSS. The results showed that the highest production of MDG was obtained from CCR cropping pattern while the lowest production from RRM cropping pattern. The Inpari 23 grown in wet season produced higher MDG (6, 092 kg ha −1 ) than Mentik Wangi which grown in dry season (5, 110 kg ha −1 ). The production of MDG has a positive correlation with plant height, dry weight of grain and weight of 1.000 grains. Since the irrigated rice fields used in this study had a moderate level of fertility, the results showed that differences in crop rotation patterns and rice cultivation techniques in irrigated rice fields that have moderate soil fertility did not affect crop productivity. The productivity have more influenced by the choice of rice varieties planted in each planting period.